Transmitter-Receiver Designs for Highly Frequency Selective Channels in MIMO FBMC Systems - Caus, M.; Perez-Neira, A. I. (IEEE transactions on signal processing, 2012)
This paper studies the MIMO applicability to filter bank based multicarrier (FBMC) modulations for low coherence bandwidth channels. Under these conditions the channel frequency response cannot be modeled flat at a subcarrier level. This implies that the techniques originally devised for OFDM do not restore the orthogonality between subcarriers when they are directly applied to FBMC. Aiming at circumventing this problem we propose the design of two MIMO FBMC schemes, which are based on a new subband processing. The figures of merit that govern the design of the first and second scheme are the signal to leakage plus noise ratio (SLNR) and the signal to interference plus noise ratio (SINR), respectively. However, we do not restrict the analysis to the design of a new subband processing but we also carry out an asymptotic analysis of the complexity as well as tackle the problem of estimating the channel. Simulation-based results have demonstrated that the addressed solutions clearly outperform previous MIMO FBMC schemes in terms of BER. In comparison to OFDM, the devised techniques are able to remain competitive even if the knowledge of the channel state information is not perfect. In those scenarios where the cyclic prefix (CP) length is not sufficiently large to avoid inter block interference, the proposed designs are able to reduce the BER. However, the price that should be paid is the increase of the complexity.